Management of the Fontan circulation in the adult patient - Clift, Paul (SA Heart Journal, 2017)
The Fontan circulation poses challenges for the patient and clinician throughout the patient’s lifetime. Given the unique physiology of the Fontan circulation, even the best Fontan patient will have a degree of exercise limitation and, with advancing years, the life threatening complications of the condition become more common. Key to the preservation of life and minimising the effects of these complications isprompt recognition and management. Patients with this complex condition require lifelong follow up in specialised units, where all members of the multidisciplinary team are experienced in managing the patients. The provision of this level of care requires planning, and in all healthcare systems where these patients are, care should be taken to develop a system of adult congenital heart disease units to facilitate the management of these and other complex cardiac conditions. This review summarises the anatomy and physiology of the Fontan circulation and provides guidance on the follow up of these patients and the complications they present with.